2017
DOI: 10.1177/0022429417716921
|View full text |Cite
|
Sign up to set email alerts
|

The Enjoyment Cycle: A Phenomenology of Musical Enjoyment of 4- to 7-Year-Olds During Musical Play

Abstract: The purpose of this phenomenological study was to describe children’s lived experience of enjoyment during musical play. Data sources included class video from 15 weeks of a 24-week extracurricular music class for 4- to 7-year-olds taught by the researcher, parent-filmed video of child participant music-making in home settings during the same period, and transcripts of exit interviews with parents and children. Participants included 12 children and 4 adults, all of whom had contributed to prior studies on chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…Agency refers to the child's control over choices, situations, and rules (see Karlsen, 2011, for a discussion of agency in music play). Researchers have conducted case studies of preschool children interacting with each other and with adults in play settings; one notable investigation focused on interactions within an early childhood music classroom (Berger & Cooper, 2003) and others included video and descriptions of play interactions at home as well as in the classroom (Koops, 2012(Koops, , 2017. Children observed in these studies exhibited playing in various groupings, with and without adults.…”
Section: Play In Musicmentioning
confidence: 99%
“…Agency refers to the child's control over choices, situations, and rules (see Karlsen, 2011, for a discussion of agency in music play). Researchers have conducted case studies of preschool children interacting with each other and with adults in play settings; one notable investigation focused on interactions within an early childhood music classroom (Berger & Cooper, 2003) and others included video and descriptions of play interactions at home as well as in the classroom (Koops, 2012(Koops, , 2017. Children observed in these studies exhibited playing in various groupings, with and without adults.…”
Section: Play In Musicmentioning
confidence: 99%
“…Teacher, students, and caregivers all enjoy a new song, new prop, or new movement activity. In a research study I conducted with a group of 4- to 7-year-old children, I found that activities were most enjoyable when a new song was paired with a known activity format, or a new activity or instrument was introduced with a known song (Koops, 2017). This scaffolding may help children feel more comfortable trying new things.…”
Section: Balance Familiarity and Noveltymentioning
confidence: 99%
“…Likewise, in a movement or conducting activity, consider what the pros and cons of building student choice into the lesson may be. Incorporating opportunities for children to express agency into the early childhood classroom could have major implications for the students as they continue through our music programs, as expression of agency is linked to motivation, which can be linked to increased learning and retention in programs (Campbell, Connell, & Beegle, 2007; Gluschankof, 2008; Green, 2008; Koops, 2017; Suthers & Niland, 2007). Expressing agency is certainly not only for early childhood classrooms either—these ideas can be extended, expanded, and applied to any music teaching and learning situation.…”
Section: Closing Thoughtsmentioning
confidence: 99%